2022
DOI: 10.46827/ejes.v9i3.4215
|View full text |Cite
|
Sign up to set email alerts
|

Instructional Policy and Quality of Business Studies Textbook in Secondary Schools in Kenya

Abstract: Meticulously developed business studies textbook facilitates individualized learning contributing to the achievement of learning objectives even in the absence of the teacher. Think-pair and share is accelerated as learners are likely to discuss amongst themselves new knowledge acquired through business studies textbook hence boosting learner enthusiasm in construction of knowledge. However, instructional information in business studies textbook may not necessarily facilitate realization of specific objectives… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The interaction between the learner and the learning materials fosters the development of abilities in a given activity, which speeds up the attainment of learning goals. According to the opinions of Bekele, Odundo, Mwangi, and Ganira (2022), a source of incentive for students' building of new knowledge may be found in business studies textbooks that offer information in a step-by-step way. Textbook on business studies with a presenting style that emphasizes the progressive development of knowledge, facilitates learning, and ultimately leads to an improvement in learning accomplishment and promotion of topic mastery.…”
Section: Instructional Content and Learning Achievementmentioning
confidence: 99%
See 1 more Smart Citation
“…The interaction between the learner and the learning materials fosters the development of abilities in a given activity, which speeds up the attainment of learning goals. According to the opinions of Bekele, Odundo, Mwangi, and Ganira (2022), a source of incentive for students' building of new knowledge may be found in business studies textbooks that offer information in a step-by-step way. Textbook on business studies with a presenting style that emphasizes the progressive development of knowledge, facilitates learning, and ultimately leads to an improvement in learning accomplishment and promotion of topic mastery.…”
Section: Instructional Content and Learning Achievementmentioning
confidence: 99%
“…When learning information is offered to the student in small increments, the learner is able to make the transition from what is known to what is unknown, which ultimately leads to the steady growth of a concept in a particular learning result. According to the opinions of Bekele, Odundo, Mwangi, and Ganira (2022), business studies textbooks that convey information in a reasonable manner have the potential to be a source of motivation for the creation of knowledge by students. Textbook on business studies with a presenting style that emphasizes the progressive development of knowledge, facilitates learning, and ultimately leads to an improvement in learning accomplishment and promotion of topic mastery.…”
Section: Introductionmentioning
confidence: 99%
“…Textbook investigation provides the publishers with a challenge to competently work on manuscripts before presented for evaluation hence resulting in quality instruction content for increased learning outcome. Additional study by Bekele, Odundo, Mwangi and Ganira [2] on teaching methods showed that systematic assessment of instruction material yields authentic and age relevant learning resource resulting in knowledge development for improved instructive achievement.…”
Section: Introductionmentioning
confidence: 99%